Between Poverty and Ngalap Berkah (Seeking for Blessings) Myth: Contradiction of Welfare Perception Among Tobbacco Farmers in di Temanggung - Abdila; Lestariningsih, Wahyu; Savana, Devina; Tunnisa, Ana Fitro; Suyatna, Hempri (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2024)
Tobacco farmers in Temanggung Regency, the largest and best tobacco producing region in Central Java, still have low incomes. However, local farmers still cultivating tobacco and believed that tobacco is a